2013
DOI: 10.1111/1471-0528.12396
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the congenital transmission of Trypanosoma cruzi: a systematic review and meta‐analysis

Abstract: Background Chagas disease is caused by the parasite Trypanosoma cruzi and endemic in much of Latin America. With increased globalization and immigration, it is a risk in any country due in part to congenital transmission. The frequency of congenital transmission is unclear. Objective To assess the frequency of congenital transmission of T. cruzi. Search Strategy PubMed, Journals@Ovid Full Text, EMBASE, CINAHL, Fuente Academica and BIREME databases were searched using seven search terms related to Chagas di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
156
0
20

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(187 citation statements)
references
References 64 publications
5
156
0
20
Order By: Relevance
“…Sosa-Estani et al [26] observed 16 women treated for Chagas disease during their childhood and found that none of their 32 infants were congenitally infected; however, transmission rates are relatively low [19], and this result would need to be confirmed by large prospective studies.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Sosa-Estani et al [26] observed 16 women treated for Chagas disease during their childhood and found that none of their 32 infants were congenitally infected; however, transmission rates are relatively low [19], and this result would need to be confirmed by large prospective studies.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Data also suggest vector control programs may potentially decrease the risk of MTCT and the severity of congenital Chagas disease by decreasing maternal parasitic load [18]. Congenital transmission rates are lower in nonendemic countries compared with endemic countries [19], and congenital Chagas disease in Bolivia has been less symptomatic in recent periods [20].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it should be noted that at this stage, treatment could lead to complete cure. Diagnosis during pregnancy and risk characterization of a given population should be seen as a window of opportunity for inquest cases of congenital Chagas 4, 7,8]. The healing of congenital Chagas disease in this critical age depends on detection during pregnancy, early diagnosis in the neonate, and quick treatment [5,9].…”
Section: Introductionmentioning
confidence: 99%